2021
DOI: 10.17691/stm2021.13.3.04
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous DNA Replication of Biallelically Expressed Genes in Human Peripheral Blood Lymphocytes as a Prognostic Sign of Cancer

Abstract: The aim of the study was to identify and quantify lymphocytes with asynchronous replication of the AURKA and TP53 genes in cancer patients versus controls and to assess the diagnostic capabilities of this approach.Materials and Methods. The study was carried out with peripheral blood lymphocytes probed for the AURKA and TP53 genes using the interphase fluorescence in situ hybridization (FISH) method (Vysis, USA and Kreatech, The Netherlands). The control group included 70 people: clinically healthy donors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Related studies have also shown high levels of AURKA as an indicator of poor prognosis in bladder cancer. It is also associated with the development and prognosis of rectal cancer, hepatocellular carcinoma, and head and neck cancer ( Lu et al, 2021 ; Tsepenko et al, 2021 ; Guo et al, 2022 ; Huang et al, 2022 ). This research discovered that high AURKA was related to a bad prognosis in various malignancies by creating a deep forest graph and feeding back the association between AURKA, overall survival, and disease-specific survival.…”
Section: Discussionmentioning
confidence: 99%
“…Related studies have also shown high levels of AURKA as an indicator of poor prognosis in bladder cancer. It is also associated with the development and prognosis of rectal cancer, hepatocellular carcinoma, and head and neck cancer ( Lu et al, 2021 ; Tsepenko et al, 2021 ; Guo et al, 2022 ; Huang et al, 2022 ). This research discovered that high AURKA was related to a bad prognosis in various malignancies by creating a deep forest graph and feeding back the association between AURKA, overall survival, and disease-specific survival.…”
Section: Discussionmentioning
confidence: 99%